Embracing Moodle for professional identity and resilience in a Cuban university during COVID-19 - Morales-Rumbaut, Diana Rosa (2023)
The last decade has been very thought-provoking and change-adapting for university professors and students in the Cuban context. On the one hand, they have faced challenges while embracing technological advances, which have positively impacted on their professional identity and resilience. On the other hand, some limitations have been evident too. In this respect, a study was carried out at the Foreign Language Teacher Education Program at "Félix Varela Morales" campus of the Universidad Central «Marta Abreu» de Las Villas, Cuba which explored how professional identity and resilience have evolved in professors and students who systematically do project work supported by the university Moodle platform. The study took place during the period 2019-2021, when the pandemic COVID-19 gave another connotation to the teaching learning process. Consequently, the use of technology was the central pivot to continue training teachers at the University, the objective of this research work was to explore the impacts of embracing Moodle platform on the professional identity and resilience in the subjects of this research through project work. The methods used in the research were data collection and data processing in a case study, which made it possible to identify the positive impacts and challenges on professional identity and resilience. The information presented was obtained from the application of document analysis, participant observation, survey, and recollection of graphic and audiovisual evidences. The results show the importance of embracing Moodle as a suitable platform in the Cuban context.